PENGARUH PENGARUH KEPERCAYAAN MEREK, KEWAJARAN HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS SUATU MEREK (STUDI KASUS TRAVEL AGENT ANTAVAYA BALI) - FREDERIK LORENSO; Ida Bagus Putu Puja (J-TRUE: Journal of Travel and Leisure, 2024)
Travel agents play a critical role in Bali's tourism industry, with Antavaya Bali being one of the largest operators. This study investigates the influence of brand trust, price fairness, and service quality on Antavaya Bali's brand loyalty. Using causal associative research and quantitative techniques, data were collected from 157 respondents and analysed with SEM PLS. The findings revealed that brand trust, price fairness, and service quality all positively and substantially impact Antavaya Bali's brand loyalty. Specifically, brand trust displayed a path coefficient of 0.233 with a t-count of 2.281 and a p-value of 0.02, price fairness demonstrated a path coefficient of 0.273 with a t-count of 3.405 and a p-value of 0.001, and service quality exhibited a path coefficient of 0.385 with a t-count of 3.535 and a p-value of 0.000. Practical recommendations are provided to enhance Antavaya Bali's brand loyalty in a competitive market. Future researchers can develop this research by using other methods to examine brand trust, price fairness, service quality, and brand loyalty of a company.